The soul of Jewish social justice - Yanklowitz, Shmuly, 1981- (Urim Publications, 2014)
The Soul of Jewish Social Justice offers a novel intellectual and spiritual approach for how Jewish wisdom must be relevant and transformational in its application to the most pressing moral problems of our time. The book explores how spirituality, ritual, narratives, holidays, and tradition can enhance one's commitment to creating a more just society. Readers will discover how the Jewish social justice ethos can help address issues of education reform, ethical consumption, the future of Israel, immigration, prison reform, violence, and business ethics.